Chronic cerebrovascular pathology: endothelial dysfunction and efficiency of superhume doses of potential antibodies to brain endogene regulators - A. P. Rachin; S. N. Vygovskaya; M. B. Nuvakhova; A. A. Voropayev; L. Yu. Tarasova; S. A. Rachin; D. V. Smirnova (Лечащий Врач, 2021)
Chronic cerebral ischemia is the syndrome of progressing multi-focal or diffusive cerebral lesion, manifested in clinical neurological, neuro-psychologic and/or mental disorders, conditioned chronic cerebral brain insufficiency and/or repeated episodes of acute disorders in cerebral blood circulation (discirculation, transitory ischemic attack, stroke).